A culture of growth : The origins of the modern economy - Mokyr, Joel (Princeton: Princeton University Press, 2017)
" The description for this book, A Culture of Growth: The Origins of the Modern Economy, will be forthcoming. "--
Includes bibliographical references (pages 343-379) and index.
Keywords: Economic development; Economic history; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Economic Conditions; BUSINESS & ECONOMICS / Economics / General; HISTORY / Europe / General